Optimalisasi Desain Struktur Organisasi dalam Meningkatkan Efektivitas Manajemen Klinik - Yohanes Kurnianto Putro; Lia Kian (Jurnal Akuntansi, Manajemen, dan Perencanaan Kebijakan, 2026)
Clinics as primary health care facilities hold a crucial role in the national health system, yet face a significant gap between the organizational structure mandated by regulations and actual field conditions. This study examines how organizational structure design optimization can improve clinic management effectiveness through three analytical dimensions namely the ideal structure prescribed by health regulations, the structural reality shaped by human resource limitations, and the operational impact of this gap. A systematic review reinforced by critical analysis and qualitative methodology was applied to literature, policies and empirical studies from 2021 to 2025. Findings indicate that most primary clinics operate with overlapping managerial roles and insufficient role separation, generating work overload, weak accountability and service inefficiency. Data shows that only 42.7% of primary health facilities achieved accreditation in the first semester of 2023, reflecting the depth of systemic gaps. Structural optimization requires competency based functional reconfiguration, technology integration and periodic evaluation. The adaptive organizational design approach is considered the most viable solution for bridging the gap between regulatory ideals and clinic operational realities in Indonesia